Indicator for Describing Bull and Bear Markets: Asymmetry and Persistence Perspective - Thampanya, Natthinee; Pornpikul, Chanapol (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2020)
This paper considers the persistent and asymmetric volatility in stock returns at each market phase in the ASEAN-5 countries. The results show that there is a prevalence of asymmetry in both bull and bear markets. Negative shocks are found to increase the volatility of stock market returns more than positive shocks. There exists a high asymmetry in bear markets whereas asymmetry is small to moderate for bull markets. Furthermore, the results suggest strong evidence of persistent volatility in all market phases. The implication for negative asymmetry and high persistence is that during market downturns, stock markets need to be monitored carefully or they should be hedged in order to limit their risk and risk-elevating impact on the financial system.